Multimedia Applications Thousand Islands Tourism Object Using Visual Basic 6.0 - Samlawi Samlawi (Jurnal Sistem Informasi, 2005)
Discussing about the world of tourism attractions, especially dikepulauan thousand who have been prepared using Visual Basic 6.0 and is expected to ease in obtaining information about natural conditions, the following panorama strengths of each, which in turn can help nature lovers, especially for tourists or research .Bibliography (1974 - 2003)